Attention in the doctor of obstetrics and gynecology teenager - Gonzáles, Carmen (2015)
Objective: To determine attention characteristics at the Adolescent Gynecology and Obstetrics Outpatient Office. Design: Observational, retrospective, longitudinal and descriptive study. Setting: Department of Obstetrics and gynecology, Cayetano Heredia National Hospital. Materials and Methods: Review of HIS 1998 and 1999 attention files of the Adolescent Gynecology and Obstetrics Outpatient Office. Results: In 3304 patients, 7,3% belonged to early adolescence, 30,2% to middle adolescence and 62,5% to late adolescence. Gynecologic pathology represented 88,4% of all diagnosis in early adolescents, 50,0% of middle adolescents and 24,2 of late adolescents. Obstetrical consultation was 7,0%, 48,4% and 75,9% of early, middle and late adolescents, respectively. Conclusions: Gynecologic pathology was the main reason of consultation in early and middle adolescents and obstetrical consultation in late adolescents.